The Factor of Political Intelligence in a Democracy - Muakchim, Nathamon (Rajapark Journal, 2026)
The purposes of this research were: (1) examine the level of opinions regarding political intelligence in a democratic system, (2) analyze the components of political intelligence in a democratic system, and (3) investigate guidelines for promoting political intelligence in a democratic system. The participants consisted of 320 eligible voters, 15 key informants, and 6 focus group participants selected through purposive sampling. The research instruments included a questionnaire with a reliability coefficient of 0.951 and a structured interview form. Data were analyzed using percentage, mean, standard deviation, exploratory factor analysis, and content analysis. The results of the research were as follows: (1) The overall level of opinions regarding political intelligence in a democratic system was high; (2) political intelligence in a democratic system comprised 12 components: political interest-seeking, political communication and information perception, political decision-making, political responsibility, democratic citizenship, critical thinking, equality and acceptance of diversity, networking and political knowledge promotion, awareness of rights, laws, and public interest, rights and freedoms in monitoring state power, political discussion and analysis, and integrity. These components jointly explained 58.103 percent of the total variance; and (3) the guidelines for promoting political intelligence should focus on three dimensions: political knowledge, political skills, and political behavior. Such development would enhance political understanding, participation, and the quality of political engagement among politicians and eligible voters within a democratic system.